2007
DOI: 10.1016/j.biomaterials.2007.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Reduced foreign body response at nitric oxide-releasing subcutaneous implants

Abstract: The tissue response to nitric oxide (NO)-releasing subcutaneous implants is presented. Model implants were created by coating silicone elastomer with diazeniumdiolate-modified xerogel polymers capable of releasing NO. The host tissue response to such implants was evaluated at 1, 3, and 6 weeks and compared to that of uncoated silicone elastomer blanks and xerogel-coated controls incapable of releasing NO. Delivery of NO (approximately 1.35 micromol/cm2 of implant surface area) reduced foreign body collagen cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
163
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 44 publications
10
163
1
Order By: Relevance
“…NO modulates tissue remodeling in party by modifying inflammatory responses and impacting angiogenesis. 26 Damaged tissues, such as infected wounds, are deficient in NO. Hence, administration of our NO-nps may enhance wound healing by facilitating bacterial killing and promoting collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…NO modulates tissue remodeling in party by modifying inflammatory responses and impacting angiogenesis. 26 Damaged tissues, such as infected wounds, are deficient in NO. Hence, administration of our NO-nps may enhance wound healing by facilitating bacterial killing and promoting collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…A major difference between our and other studies [16][17][18] is the porous nature of the surgical meshes evaluated in comparison with bulk silicone rubber implants. The porosity of surgical meshes is nowadays adapted to allow macrophage penetration through its pores.…”
Section: Discussionmentioning
confidence: 53%
“…A number of studies have evaluated the effects of NO in vivo, as released from nitrogen-based (N-based) polymer coatings, such as N-based diazeniumdiolate coatings. Beneficial effects in vivo have been found on wound healing and tissue integration [16][17][18], as well as a remarkable decrease in bacterial presence on biomaterial surfaces [19]. However, a major disadvantage associated with all Nbased diazeniumdiolates is their potential to form carcinogenic nitrosamines upon decomposition [20].…”
Section: Introductionmentioning
confidence: 98%
“…71,72 Since NO is a gas, its storage and delivery has been achieved using NO donors. 73,74 A number of macromolecular scaffolds capable of NO storage and delivery have been reported, including xerogels, [75][76][77] silica nanoparticles, [78][79][80] dendrimers, 81,82 micelles, 83 NO donor-doped polymer matrices, [84][85][86] and synthetic polymers. [87][88][89] The NO release trigger depends on the NO donor employed but may be as simple as water or heat.…”
Section: Active Releasementioning
confidence: 99%
“…70 With respect to mitigating the FBR, Hetrick and associates 75 reported a reduced inflammatory response, thinner capsule formation, and greater blood vessel formation for NO-releasing subcutaneous implants at extended periods (weeks) despite only 72 h of measureable NO release. 75 In subsequent work, Gifford releasing glucose sensor was characterized by a reduced run-in time (i.e., time required to stabilize sensor response after implantation). 71 While sensor success with only initial NO release was accomplished, Nichols and colleagues 90 showed that NO-releasing microdialysis probes further enhanced in vivo glucose recovery compared with controls over longer periods (up to 14 days).…”
Section: Active Releasementioning
confidence: 99%